Feasibility of a novel tacking method of securing mesh in transabdominal preperitoneal inguinal hernia repair: Secure tacking against recurrence. Issue 4 (19th February 2018) - Nagahisa, Yoshio; Kawashima, Ryuju; Matsumoto, Ryu; Harada, Masaki; Hashida, Kazuki; Okabe, Michio; Kawamoto, Kazuyuki
Abstract: Introduction: Postoperative chronic pain is an important outcome of hernia surgery. In laparoscopic hernia surgery, either fixation outside the trapezoid of disaster or no fixation is recommended to avoid postoperative pain. To avoid recurrence are transabdominal preperitoneal (TAPP) hernia repair, the myopectineal orifice must be covered with mesh during TAPP, but lifting or shrinking of the mesh can lead to recurrence. The aim of this study was to evaluate the feasibility of a novel technique for mesh fixation to prevent the mesh from lifting off. Methods: After the preperitoneal space was created during TAPP, the anatomy of the lateral cutaneous nerve of the thigh or the femoral branch of the genitofemoral nerve within the trapezoid of disaster was checked. The mesh was tacked at the trapezoid of disaster without nerve injury, and the mesh was fixed with circumferential tacking. We call this procedure secure tacking against recurrence (STAR). We treated 391 adult patients (478 hernias) with TAPP repair; novel tacking was used in some patients (STAR group, 236 hernias). The results of the STAR group were retrospectively compared with those of patients in whom we did not use this novel tacking (conventional group, 242 hernias). Results: There was no postoperative chronic pain in either group. There were no cases of hernia recurrence in the STAR group, but there were four cases of hernia recurrence in the conventional group (0% vs 1.7%, P = 0.047). These four recurrences consisted of indirect hernia and mesh lifting on the lateral side. Conclusion: The STAR procedure is feasible and safety as a standard procedure for securing the mesh during TAPP.